2016
DOI: 10.1002/ejic.201501429
|View full text |Cite
|
Sign up to set email alerts
|

The Developing Concept of Bifunctional Catalysis with Transition Metal N‐Heterocyclic Carbene Complexes

Abstract: Though N-heterocyclic carbenes (NHCs) have long become popular as ligands of choice in transition metal mediated homogeneous catalysis, their related utility in bifunctional catalysis remains surprisingly overlooked. Conceptually more challenging, the bifunctional catalysis requires synchronous activations of substrates at complementary active-sites of a carefully crafted catalyst architecture, and which has been success- (Brookhaven National Laboratory, 1998-2001 and Professor Guillermo C. Bazan (University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 114 publications
0
26
0
Order By: Relevance
“…Despite their promise, the multistep sequences required for the synthesis of these fused bicyclic oxazolidine N‐heterocyclic carbene ligands has somewhat restricted the larger applicability of these ligands, and this has attracted our attention. Specifically, owing to our interest in the exploration of the catalytic utility N‐heterocyclic carbene ligands with different ring types, spanning from the ubiquitous five‐membered cyclic imidazole‐ and triazole‐based ones to less common varieties such as acyclic six‐membered N‐heterocyclic carbenes, bicyclic imidazo[1,2‐ a ]pyridines,, and tricyclic triazolooxazine‐derived ones, we became interested in exploring the catalytic exploits of one such less frequently encountered type, that is, chiral bicyclic oxazolidine‐fused N‐heterocyclic carbene ligands. Furthermore, as much of the catalytic studies reported for these bicyclic oxazolidine‐fused N‐heterocyclic‐carbene‐based systems were performed under in situ LAC conditions and there are no known examples of well‐defined transition‐metal complexes, we decided to employ structurally characterized molecular complexes for our study in asymmetric catalysis to obtain a better insight into the mode of action of these catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their promise, the multistep sequences required for the synthesis of these fused bicyclic oxazolidine N‐heterocyclic carbene ligands has somewhat restricted the larger applicability of these ligands, and this has attracted our attention. Specifically, owing to our interest in the exploration of the catalytic utility N‐heterocyclic carbene ligands with different ring types, spanning from the ubiquitous five‐membered cyclic imidazole‐ and triazole‐based ones to less common varieties such as acyclic six‐membered N‐heterocyclic carbenes, bicyclic imidazo[1,2‐ a ]pyridines,, and tricyclic triazolooxazine‐derived ones, we became interested in exploring the catalytic exploits of one such less frequently encountered type, that is, chiral bicyclic oxazolidine‐fused N‐heterocyclic carbene ligands. Furthermore, as much of the catalytic studies reported for these bicyclic oxazolidine‐fused N‐heterocyclic‐carbene‐based systems were performed under in situ LAC conditions and there are no known examples of well‐defined transition‐metal complexes, we decided to employ structurally characterized molecular complexes for our study in asymmetric catalysis to obtain a better insight into the mode of action of these catalysts.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Moreover, the modulation of its N-substituents can also fine-tune the steric and electronic properties of the NHCs. 10 As a result, the transition metal complexes of NHCs have been extensively studied in homogeneous catalysis. 11 Along this line, catalytic ester hydrogenation processes using well-defined metal–NHC complexes have started evolving in recent times.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, we become interested in exploring the utility of well‐defined transition metal N‐heterocyclic carbenes as precatalysts for the condensation reaction, in tune with our larger interest in the application of transition metal N‐heterocyclic carbene complexes in homogeneous catalysis reactions and in biomedical applications . In this regard, we have recently reported the utility of the coinage metals like the Au(I/III) N‐heterocyclic carbene complexes for the β‐enaminone synthesis and proceeding further along the line we set out to explore the potential of the Fe‐NHC complexes in the synthesis of β‐enamino compounds.…”
Section: Introductionmentioning
confidence: 99%